The traditional Malay mosque : design and construction / Ilyana Sujak, Anuar Talib and Norashikin Abd. Karim - Sujak, Ilyana; Talib, Anuar; Abd. Karim, Norashikin (2012)
The mosque architecture has always been symbolized as the past culture, building technologies and community values of the local traditional Islamic community. Differ from the traditional time, modern mosques which do not incorporate local community participation have resulted detachment of the society from the mosque. The modern society is no longer mengimarah (frequented) the mosque as previously performed by the traditional community. Therefore, acquaintance on the basic principles of the traditional Malaysian mosque construction is essential to discover the bond between the society and its mosque architecture. It is critical to identify and understand the concept of design and construction of traditional mosques particularly in the aspect of building components and materials, method of construction, passive design application as well as the community participation in order to design better mosques for the Muslim communities in the future.